Analysis of Rock Layering Structure Using Shear Wave Velocity from HVSR Inversion - Delpa Astuti; Refrizon Refrizon; Arif Ismul Hadi; Muhammad Najib Syami Muqtadir (Journal of Technomaterial Physics, 2026)
The Musi Ujan Mas Hydropower Plant (HPP) area in Kepahiang lies within an active tectonic zone influenced by the Sumatra Fault, making it prone to earthquakes. This study aims to analyze subsurface rock structures and seismic vulnerability using shear wave velocity derived from the Horizontal to Vertical Spectral Ratio (HVSR) inversion method with TerraWareHV software. Microtremor data were collected at 40 measurement points, each recorded for approximately 30 min. HVSR analysis was used to derive the dominant frequency ( ) and amplification factor ( ), which were subsequently used to generate shear wave velocity models . The results show that the  values range between 1.28 and 5.55 Hz, with most locations characterized by low frequencies associated with thick sediment layers and weak soil materials. The values vary between 2.99 and 16.86,  with higher amplification observed in areas composed of less compact lithology. The inversion results indicate noticeable variations in shear wave velocity with depth, suggesting heterogeneous subsurface conditions. The study area is predominantly composed of thick sediment layers with moderate to high amplification potential. These findings provide valuable insights into local site effects and support seismic hazard assessment and infrastructure development in the region.